Exploration of Magnetohydrodynamic (MHD) Mixed Convective Flow over a Vertical Porous Surface, Accounting for Viscous Dissipation. (International Journal of Food and Nutritional Sciences, 2021)
This investigation delves into the combined influences of thermal radiation and chemical reaction on the steady mixed convective flow of heat and mass transfer in the presence of magnetohydrodynamics (MHD). The scenario involves a semi-infinite vertical porous plate subject to Joule heating and viscous dissipation. The governing set of partial differential equations (PDEs) is transformed into a non-dimensional form using dimensionless variables. These non-dimensional equations are subsequently solved numerically employing a two-term perturbation technique. The study examines the impact of various parameters within the problem on the distribution of dimensionless velocity, temperature, and concentration profiles across the boundary layer.